2020
DOI: 10.3390/polym12040877
|View full text |Cite
|
Sign up to set email alerts
|

Uncommon Sorption Mechanism of Aromatic Compounds onto Poly(Vinyl Alcohol)/Chitosan/Maleic Anhydride-β-Cyclodextrin Hydrogels

Abstract: Aromatic hydrocarbons are extensive environmental pollutants occurring in both water and air media, and their removal is a priority effort for a healthy environment. The use of adsorbents is among the several strategies used for the remediation of these compounds. In this paper, we aim the synthesis of an amphiphilic hydrogel with the potential for the simultaneous sorption of a set of monocyclic and polycyclic aromatic hydrocarbons associated with toxicity effects in humans. Thus, we start by the synthesis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 81 publications
0
3
0
1
Order By: Relevance
“…4F showed that the storage modulus ( G ′) of both two groups was more significant than the loss modulus ( G ′′) over the entire strain range of 0.01–100%, indicating the solid-like rheological properties of the hydrogels and their ability to retain the shape after crosslinking. 27,28…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4F showed that the storage modulus ( G ′) of both two groups was more significant than the loss modulus ( G ′′) over the entire strain range of 0.01–100%, indicating the solid-like rheological properties of the hydrogels and their ability to retain the shape after crosslinking. 27,28…”
Section: Resultsmentioning
confidence: 99%
“…4F showed that the storage modulus (G 0 ) of both two groups was more significant than the loss modulus (G 00 ) over the entire strain range of 0.01-100%, indicating the solid-like rheological properties of the hydrogels and their ability to retain the shape after crosslinking. 27,28 3.6 3D printed hydrogel scaffolds DECM hydrogel is well known for its poor mechanical properties. In this experiment, we improved the mechanical properties of DECM by increasing the concentration of the bio-ink and controlling the temperature of the printing abutment.…”
Section: Rheological Analysis Of Bio-inksmentioning
confidence: 99%
“…A versatilidade das ciclodextrinas, a sua reatividade e a facilidade em formar compostos supramoleculares em solução, conduziu ao aumento das áreas de aplicação através da sua utilização em estado sólido. As ciclodextrinas podem ser modificadas por reticulação ou por ligação covalente de moléculas de CDs a uma matriz insolúvel preexistente (por exemplo, polímeros sintéticos altamente reticulados, alginato, quitosano, nanofibras e zeólitos) [19,[50][51][52]. Polímeros à base de CDs (Figura 1b), e CDs enxertadas ou revestidas em matrizes insolúveis (Figuras 1c e 1d) têm encontrado aplicações de relevo em áreas como a remediação ambiental, biomédica e farmacêutica [53][54][55][56].…”
Section: Ciclodextrinasunclassified
“…Due to large steric hindrance, it is difficult to form the homo-polymer of maleic anhydride; however, copolymerization based on maleic anhydride is very common, and many copolymers containing maleic anhydride have been prepared and applied in scale inhibition and dispersing agents. As one of the hydrophilic monomers, maleic anhydride (MA) is often used in the preparation of hydrogels [ 26 , 27 , 28 ]. Furthermore, MA is easy to modify and functionalize for the copolymers containing maleic anhydride through the reaction of acid anhydride groups and other functional groups [ 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%